Effect of Sox9 on TGF-β1-mediated atrial fibrosis. (1st October 2021) - Wang, Hechuan; Chen, Yiqi; Zhao, Shuting; Wang, Xiaowen; Lu, Kai; Xiao, Hua
Abstract: Atrial fibrosis is a crucial mechanism responsible for atrial fibrillation (AF). Sex-determining region Y-box containing gene 9 (Sox9) plays a pivotal role in fibrosis of many organs such as the skin, kidney, and liver. However, there are few studies about the occurrence and maintenance of Sox9 in atrial fibrosis. In this study, we investigated the role of Sox9 in the fibrotic phenotype of human atrial tissues and rat atrial fibroblasts in vitro . In the human right atrial tissue, Masson's trichrome staining, immunofluorescence, real-time quantitative polymerase chain reaction, and western blot analysis were carried out to explore the relationship between Sox9 and atrial fibrosis at the morphological, functional, and molecular levels. In cultured atrial fibroblasts, Sox9 was overexpressed by adenovirus or depleted by siRNA, and then, recombinant human transforming growth factor (TGF)-β1 was added. Immunofluorescence analysis, western blot analysis, Transwell assay, and scratch assay were used to analyze the cells. In patient atrial tissues, Sox9 was increased with worsened atrial fibrosis, and this increase was related to AF severity. In rat atrial fibroblasts, Sox9 was promoted by TGF-β1, and the α-smooth muscle actin (α-SMA) protein level and the ability of cell migration were increased after Sox9 overexpression by adenovirus, while the α-SMA protein level and the cell migration ability were decreased after Sox9 depletion by siRNA. In conclusion, Sox9 is involved in the regulation of fibrosis in the atria and may be located downstream of TGF-β1. Our findings may provide a new perspective to treat atrial fibrosis during AF.